Analysis of Poverty in Kulon Progo DIY - Rina Oktavia; Latri Wihastuti (Universitas Ahmad Dahlan, Yogyakarta, 2022)
Kulon Progo Regency is one of the regencies in the Special Region of Yogyakarta which has a very high percentage of poverty rates. The problem of poverty in Kulon Progo Regency has not yet been resolved. In fact, compared to other regencies/cities in the Special Region of Yogyakarta, the percentage of poor people in Kulon Progo Regency ranks the highest. Various poverty reduction policies have been carried out by the district and provincial governments to reduce poverty rates, but still have not shown significant results. This condition is interesting to analyze considering that poverty policies have not yet had an impact on the condition of Kulon Progo. The purpose of this study was to determine the determinants of poverty in Kulon Progo. This study uses a mixed research approach, namely research that combines quantitative and qualitative research approaches. The results of this study indicate that the inherent characteristics of households in Kulon Progo affect the level of poverty.